Malayan Railway. Future prospect of timber and logs traffic / Md. Mazlan Abd Halim - Abd Halim, Md. Mazlan (1986)
Timber and logs' is one of the major commodities carried by the Malayan Railway, but the total tonnage moved has been decreasing from 470 019 tonnes in I98O to 273 289 tonnes in 1984. However we should take into consideration the recession period that has affected the overall production of logs since 1980. MR's market share has suffered a drop during the period of 1980 to I984. During this five years the average market share for logs and sawn timber were 5.36$ and 0.45$ respectively. MR has been concentrating on the long distance traffic. The average distance carried per tonne for logs and sawn timber were 252 1cm and 432.9 km respectively. For the past five years at the average, 99$ of the traffic originated from Kelantan. In the years to come, the states' policy on the movement of logs from their respective state will not favour MR since the restriction on the movement of logs especially from Kelantan will surely effect MR as a carrier. MR itself has been subjected to many problems in the movement of timber and logs, especially on the wagons supply when it suffered a high percentage of sick wagons at the average of 35$' Therefore during this difficult period MR should improve on their performance especially on their customers' service which have been very poor, in order to gain more traffic and at the same time increase their market share.